Implementasi Instrumen Tes Objektif Berbasis HOTS dalam Evaluasi Pembelajaran PAI di SMA Negeri 1 Jetis Bantul - Arya Pramudita; Wahyu Kholis Prihantoro; Naqiyatul Fikriyah; Luthfi Falasifah; Safa’atun Nursolihah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Learning evaluation is an important element in the educational process because it allows us to determine the extent to which students have achieved their competencies and helps improve the quality of learning. Objective tests are considered relevant because they can measure students' thinking abilities efficiently and systematically. However, in PAI learning, there are challenges because what is assessed is not only knowledge, but also understanding, attitudes, and actions in religion. This study aims to analyze the application of objective test instruments in evaluating PAI learning at SMA Negeri 1 Jetis Bantul, including how teachers create questions, the difficulties they encounter, and the impact on students. This study uses a qualitative approach with interview, observation, and documentation techniques, then content analysis is used to analyze the results. The findings indicate that teachers have applied HOTS-based questions in accordance with the principles of the Merdeka Curriculum. However, students still have difficulty understanding long narrative questions, and objective instruments are not appropriate for assessing affective aspects. In general, students respond positively, but their learning style tends to be instant, relying solely on question outlines. To achieve holistic educational goals in line with the Pancasila Student Profile, continuous innovation is needed in the development of objective testing instruments that are capable of comprehensively measuring cognitive, affective, and psychomotor aspects.